Punching shear behaviour analysis of RC flat floor slab-to-column connection - Vainiūnas, Povilas; Popovas, Vladimiras; Jarmolajev, Andrei (Journal of Civil Engineering and Management, 2002)
The paper presents information about theoretical investigations and based on computer modelling and analysis research methods of flat floor slab-to-column joint behaviour for punching” obtained by authors. Main principles of calculation and design methods of flat slab-to-column support under punching according to variety of international design coded are observed and compared. The design problems of beamless floor systems for shear with bending are discussed. The set of variables, such as lateral flexural reinforcement, bending moment to shear force ratio, span-to-slab depth ratio and slab thickness to column depth ratio, which may have an influence on flat two-ways floor slab punching shear strength is established and computer modelling analysis methods are applied to investigate the problem.Frist Published Online: 30 Jul 2012